John F. Dillon, The Revised Ordinances of the City of Davenport 145 (1866) - (:unkn) unknown (My University, 1855)
Ch. 19, § 1-2: Prohibited discharge of any gun, pistol, or other firearms. Also prohibited discharging firecrackers, rockets, or any other description of fireworks. Violators fined not less than two nor more than ten dollars for each offense.
Keywords: DISCHARGE